CD137 Agonists Targeting CD137-Mediated Negative Regulation Show Enhanced Antitumor Efficacy in Lung Cancer - Yi, Ling; Jin, Xin; Wang, Jinghui; Yan, Zhuohong; Cheng, Xu; Wen, Tao; Yang, Bin; Wang, Xiaojue; Che, Nanying; Liu, Zhidong; Zhang, Hongtao (Frontiers in Immunology, 2022)
Background Negative immune regulation is notable in tumor immunity. This study aimed to validate that CD137 mediates negative immunoregulation as well as agonist activity in tumor immunity. Methods sCD137 (soluble CD137), a prominent splice variant of mCD137 (membrane-bound CD137), was identified, and its blood concentration was determined in lung cancer patients using sandwich ELISA and RT-PCR. The enrichment of CD137+ Tregs (regulatory T cells) and their potential immunosuppressive activity were evaluated by ARMS-QPCR, flow cytometry and RNA sequencing. The associations between CD137+ Tregs and OS (overall survival) were analyzed retrospectively by multiplexed QIF (quantitative immunofluorescence). The therapeutic efficacy of targeting CD137+ Tregs with two types of CD137 agonists, either mIGg2a or its Fc-silenced isotype, was evaluated in two mouse tumor transplantation models. Results We found that the concentration of sCD137, a negative regulator, was increased in the blood of patients with lung cancer. In particular, CD137+ Tregs enriched in the tumor site exhibited high inhibitory activity and were amplified. Moreover, a high frequency of CD137+ Tregs in tumors was associated with worse OS, and targeting CD137+ Tregs clearly decreased both CD137+ Tregs and total Tregs, improved the antitumor efficacy of CD8+ T cells and prolonged survival in tumor transplantation models. Conclusion We confirmed the high inhibitory activity of CD137+ Tregs in lung cancer and elucidated the molecular basis for this activity. Notably, a CD137 agonist able to eliminate CD137-mediated negative regulation showed enhanced antitumor efficacy.